CURRENT STATE OF HYDROGEOLOGICAL STUDY OF MINERAL RADON WATER DEPOSITS IN THE ZHYTOMYR REGION OF UKRAINE - SHARIKOV, Sergii; CHOMKO, Dmytrо (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Radon is a radioactive chemical element that belongs to the category of inert gases. Radon water treatment (for external and internal use) has been used in various parts of the world (Austria, Poland, Germany) for more than 100 years. In medical practice, radon baths are mainly used to relieve pain, relax, relieve tension, normalize blood pressure and strengthen blood vessels. Within the Zhytomyr region, since the "Soviet times", work has been carried out to search for and evaluate mineral radon water deposits. The explored deposits within Zhytomyr region require further deeper study and systematization, because, taking into account the demand for mineral radon waters in the "pre-water" period, we predict a gradual recovery of demand in post-war times, including medical tourism. An analysis of stock materials for the search and evaluation of mineral radon waters within Zhytomyr region was carried out. The systematization of data was carried out and the quality indicators of mineral radon waters in explored deposits were studied. At the moment, there are many medical institutions in Ukraine that provide professional and specialized care using mineral radon groundwater. We can state that mineral radon waters are an integral part of the treatment base of many sanatoriums in Ukraine (sanatoriums in the cities of Khmilnyk, Nemyriv, the village of Denishi, etc.). In the Zhytomyr region, the most famous is the Denyshiv deposit of mineral radon waters, on the basis of which the "Denyshi" sanatorium operates. The potential for the development of more detailed hydrogeological research of the already explored deposits of the Zhytomyr region is high. Balneological properties and chemical composition of underground waters have not been sufficiently studied at the moment. This is explained by the fact that industrial production of mineral radon waters takes place within the Zhytomyr region from only one deposit. Funding for further geological exploration (geophysical, geological, hydrogeological) work on the search and exploration of new deposits or within the limits of the distribution zones of mineral radon waters is quite promising today.
Keywords: radon; gas; mineral radon groundwater; Zhytomyr region; deposit; reserves